Apakah Kualitas Audit Memediasi Ukuran Perusahaan dan Audit Fee terhadap Opini Audit Going Concern ? - Eliza Virginia; Rosidi Rosidi; Zaki Baridwan (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to determine the effect of company size and audit fees on going concern with audit quality as a mediating variable. Methodology/approach: The data used in this study came from questionnaires distributed at KAP Big Ten. The test used in this study is PLS. Findings: The results showed that (1) company size has a negative effect on going concern; (2) audit fee has a positive effect on going concern; (3) audit quality has a positiveffect on going concern; (4) company size has no effect on audit quality; (5) audit fee has a positive effect on audit quality; (6) company size has a negative effect on going concern opinion mediated by audit quality; (7) audit fee has a positive effect on going concern opinion mediated by audit quality. Practical and Theoretical contribution/Originality: This research can provide practical guidance for management in obtaining and providing additional information that needs to be disclosed when a company is at risk of facing issues regarding the continuity of its operations. For auditors, this research can offer guidance in evaluating policies or performance to maintain and improve the quality of services provided. Furthermore, this research can explain existing theories within the research phenomenon, namely decision-making theory (Simon, 1993) and DeAngelo's quality theory (1981), and provide empirical evidence regarding several factors that affect going concern. Research Limitation: The limitation of this research lies in the low participation rate of respondents in filling out the questionnaires sent. The level of busyness, especially among auditors, is the main obstacle that causes the low response rate to the questionnaires.